Multivariant nature of displacive transitions in copper based shape memory alloys - Adiguzel, Osman (My University, 2012)
Shape memory effect is an unusual property exhibited by certain alloy systems, and based on a displacive transition, martensitic transition. Copper based alloys exhibit this property in metastable b-phase region and bcc-based high temperature parent phase structures martensitically turn into the layered complex structures on cooling from high temperature. Martensitic transformations occur with cooperative movement of atoms by means of lattice invariant shears on a {110}-type plane of austenite matrix which is basal plane of martensite. The lattice invariant shears occurs, in two opposite directions, <110 >-type directions on the {110}-type basal plane. This kind of shear can be called as {110}<110>-type mode, and possible 24 martensite variants occur. This lattice invariant shear gives rise to the formation of layered structure. Product martensitic phase has the unusual layered structures which consist of an array of close-packed planes with complicated stacking sequences called as 3R, 9R or 18R martensites depending on the stacking sequences on {110}-type planes of parent phase. The basal plane of martensite is subjected to the hexagonal distortion with martensite formation on which atom sizes have important effect. It is known that the local stress and composition conditions can play an important role in the final structures of the material.
4th International Conference on Advanced Materials and Systems, ICAMS 2012 -- 27 September 2012 through 29 September 2012 -- Bucharest -- 100613
Keywords: Bain distortion.; Martensite variants; Martensitic transition; Shape memory effect